2005
DOI: 10.1097/01.inf.0000180578.38584.da
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and 24-Week Efficacy/Safety of Dual Boosted Saquinavir/Lopinavir/Ritonavir in Nucleoside-Pretreated Children

Abstract: Plasma drug concentrations of saquinavir, lopinavir and ritonavir were at the higher limits of expected ranges for adult treatment at approved dosages (1000/100 mg bid for saquinavir, 400/100 mg bid for lopinavir/ritonavir). The regimen was well-tolerated and had good efficacy at 24 weeks. This dual boosted protease inhibitor combination should be assessed in larger trials of reverse transcription inhibitor-experienced children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…A published PK/PD analysis on the relation between LPV concentration and effect in patients receiving these doses, as well as 800/200 q.d., states that no relation between drug concentration and antiretroviral effect was observed within the range of LPV exposures investigated [35]. The direct clinical evidence cited for the suggested efficacy cut-off of 1,000 ng/ml in treatment-naïve patients appears to be restricted to a study of 20 children with prior NRTI experience, who were treated with a dual-boosted PI regimen, including saquinavir and LPV [36]. Our study was unable to validate this cutoff; indeed, since only one of 49 samples was below this level, we were unable to test it at all.…”
Section: Discussionmentioning
confidence: 99%
“…A published PK/PD analysis on the relation between LPV concentration and effect in patients receiving these doses, as well as 800/200 q.d., states that no relation between drug concentration and antiretroviral effect was observed within the range of LPV exposures investigated [35]. The direct clinical evidence cited for the suggested efficacy cut-off of 1,000 ng/ml in treatment-naïve patients appears to be restricted to a study of 20 children with prior NRTI experience, who were treated with a dual-boosted PI regimen, including saquinavir and LPV [36]. Our study was unable to validate this cutoff; indeed, since only one of 49 samples was below this level, we were unable to test it at all.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of SQV might further enhance the efficacy of salvage therapy for patients who had previously failed multiple ARV regimens (1). In this study, subjects treated with NNRTI in addition to LPV/r and SQV had better virologic (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…The dose of SQV chosen for this study is higher than the directly scaled adult dose (1,000 mg/1.73 m 2 ϭ 578 mg/m 2 ) but was chosen because prior studies of SQV in children had suggested high oral CL (1,12,22,34,38). Our subjects had higher SQV exposures than adults treated with SQV and standard doses of LPV/r, which is perhaps from the higher doses of LPV/r used in this study.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…41 An earlier study by the same group found that the pharmacokinetic profile of this regimen was favorable in children. 42 However, APV or SQV in combination with LPV/r have fallen out of favor in recent years due to the side-effect profile on lipids as well as due to the high pill-burden, leading to a risk of reduced adherence. In addition, results on pharmacokinetic interactions of APV and LPV/r have produced conflicting results.…”
Section: Discussionmentioning
confidence: 99%